Pengaruh Media Pembelajaran Mind Map Terhadap Kemampuan Berpikir Kritis Anak Usia Dini - Annisa Failasufa; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2024)
This study aimed to measure the effect of using mind map learning media on the critical thinking skills of early childhood children, as well as to analyze the differences in critical thinking skills before and after the implementation of mind map learning media. This study employed a pre-experimental research design with a pretest-posttest on one experimental group consisting of group B children at TK Negeri 1 Labuapi. Data on children's critical thinking skills were collected through observation and documentation, then analyzed using the N-Gain test and hypothesis testing to determine the effectiveness level of using mind maps. The results showed a significant effect of using mind map learning media on improving the critical thinking skills of early childhood children, evidenced by an average N-Gain value of 0.72, indicating a high level of effectiveness and significant hypothesis test results (p < 0.05). Furthermore, there was a significant difference between the pretest and posttest results, reinforcing this finding. Thus, mind map learning media has an impact on the critical thinking skills of early childhood children. Therefore, it is recommended to implement this media more widely in the learning process at the early childhood education level to create a more interactive, enjoyable, and meaningful learning experience for children.